Utilization of Whatsapp Business in Marketing Strategy to Increase the Number of Sales Through Direct Interaction with Customers - Raodatul Jannah (Syntax Idea)
In the business world, effective communication is essential to achieve success in establishing relationships with clients, business partners, and co-workers. In today's ongoing digital age, technology has changed the way we communicate making it easier for individuals or groups to connect with each other remotely. One of the most popular chat apps today is WhatsApp, and in the business world, WhatsApp Business can provide many benefits. The purpose of this study is to provide an overview of what features can be used on WhatsApp Business for business purposes. The data collection method used in this study is to use secondary data, namely through literature review obtained from journals or supporting articles. WhatsApp Business offers a variety of features, such as contact lists, sending messages with interesting content, using automated messages, offering special promotions, and providing customer support. These features are very useful in increasing sales, saving time and effort, and maintaining consistent communication with customers.